The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/jsap.12600
|View full text |Cite
|
Sign up to set email alerts
|

Design of an intraocular pressure curve protocol for use in dogs

Abstract: Summary:Objectives:To establish an intraocular pressure curve protocol that is safe for corneal health and determining if they detect harmful elevations of intraocular pressure outside normal clinic hours. To determine inter-user variability and if repeated measurements affect intraocular pressures.Methods: Dogs with glaucoma were included in the first part of the study in which intraocular pressures were measured using three protocols. Protocol 1 used applanation tonometry every two hours over 24h. Protocols … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…Although a fluorescein test was not performed, slit examination did not detect epithelial changes that could have influenced tear stimulation. This is in agreement with previous investigations in dogs, which did not report corneal side effects of serial STT‐1 readings and rebound tonometry measurements …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although a fluorescein test was not performed, slit examination did not detect epithelial changes that could have influenced tear stimulation. This is in agreement with previous investigations in dogs, which did not report corneal side effects of serial STT‐1 readings and rebound tonometry measurements …”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with previous investigations in dogs, which did not report corneal side effects of serial STT-1 readings 30,60,63 and rebound tonometry measurements. 57,65 In conclusion, the present study has shown that the sedative effect resulting from the intramuscular administration of 0.2 mg/kg of butorphanol was not associated with any change in the position of the globe and nictitating membrane, did not appear to influence the results of the basic tests of the neuro-ophthalmic examination, and did not modify basal tear secretion. The findings also suggest that the opioid can affect reflex tear production, IOP, and pupil size, which is in agreement with previous studies.…”
Section: Discussionsupporting
confidence: 45%
“…The prevalence of POH in rabbits is unknown. Three of the 13 operated rabbits in the present study had their IOPs measured for more than 12 h postoperatively using a previously described IOP‐curve protocol, and none developed POH during that time. The rest of the rabbits had very brief hospital stays (approximately 6 h), and none developed POH during that time.…”
Section: Discussionmentioning
confidence: 46%
“…The first three operated rabbits (P1‐P3) stayed overnight and underwent serial intraocular pressure (IOP) measurements to assess for postoperative hypertension (POH) following an established protocol . None of the three rabbits developed POH during that time.…”
Section: Resultsmentioning
confidence: 99%
“…Review of major clinical trials in humans suggests that the IOP variations themselves (versus simply the magnitude of the IOP increase) may be an independent risk factor for the progression of glaucoma 7 . Recently, Sanchez et al demonstrated that rebound tonometry every 3 hours for 30 hours found increased IOP in 40% of patients that a single IOP measurement during regular clinic hours would not have identified 8 . This suggests that treatment modalities that more consistently blunt short‐ and long‐term variability in IOP may improve patient outcomes.…”
Section: Introductionmentioning
confidence: 99%